2011
DOI: 10.1111/j.1467-8535.2010.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Game‐based feedback for educational multi‐user virtual environments

Abstract: The authors of this paper are based at the University of Ulster in Northern Ireland. Darryl Charles specialises in computational intelligence for games and virtual worlds. Michael McNeill is interested in graphics algorithms and interaction within the same context. Therese Charles is currently completing her PhD studies in the area of game based learning, under the supervision of Dave Bustard and Michaela Black, who have an interest in innovative approaches to e-learning and teaching in general. AbstractIt is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 4 publications
(11 reference statements)
3
62
0
6
Order By: Relevance
“…As shown in Table 1, below the number of participants in the studies ranged from 14 to 371 with five studies (Abramovich et al, 2013;Charles et al, 2011;Gåsland, 2011;Meyer, 2008;O'Donovan, Gain & Marais, 2013) having fewer than 50 participants.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 1, below the number of participants in the studies ranged from 14 to 371 with five studies (Abramovich et al, 2013;Charles et al, 2011;Gåsland, 2011;Meyer, 2008;O'Donovan, Gain & Marais, 2013) having fewer than 50 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Points can be awarded for a wide variety of tasks such as completing quizzes, attending lectures, taking part in class exercises, solving puzzles, creativity in assignments (Charles et al, 2011;O'Donnell et al, 2013), completing practice questions, or correct answers (Mekler et al, 2013a). Mekler et al (2013a) discovered that awarding points was effective in increasing intrinsic motivation.…”
Section: Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-time feedback helps users to identify their weaknesses during their performance (Lopez et al, 2012) and to continuously adapt their behavior to efficiently reach training goals. Previous research has demonstrated that effective feedback systems should reinforce the gamification aspects of the training, which is based on the gradual increase of challenges, perceptual support, and finely tuned scoring systems (Charles et al, 2011;Honey and Hilton, 2011). However, how best to provide effective feedback within an immersive CRM training system remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Given that some students perceive an inherent tension between cultivating a fun versus a scholarly atmosphere, instructors may wish to explain the measured benefits of gamification to learning so that it is not merely perceived as an unwelcome distraction [14], [15]. In addition, despite the ability for competition to increase student engagement [16], caution may need to be exercised to ensure the competitive dynamic does not result in students feeling disempowered Figure 2. Improvement in course content mastery between the first and last weeks of class as assessed by 7 multiple-choice questions (n = 103 students).…”
Section: Discussionmentioning
confidence: 99%